Psychometric evaluation of the Chinese version of the BENEFITS-CCCSAT based on CTT and IRT: a cross-sectional design translation and validation study - Chuang Li; Chuang Li; Youbei Lin; Betul Tosun; Pin Wang; Hong Ye Guo; Cheng Rong Ling; Ran Qi; Qing Yue Luo; Yan Wang; Fang Huang; Jiaqi Wang; et al. (Frontiers in Public Health)
BackgroundThe importance of culturally competent care in multicultural environments is increasingly recognized; however, effective tools to assess nursing students’ cross-cultural competence remain limited. This study aimed to validate the BENEFITS-CCCSAT for Chinese nursing students.MethodsThe original BENEFITS-CCCSAT was translated, back-translated, culturally adapted, and pre-tested using the Brislin model to form a Chinese version. A combined approach of classical test theory (CTT) and item response theory (IRT) was then used for multidimensional validation.ResultsThe CTT analysis showed that the C-BENEFITS-CCCSAT had a Cronbach’s α coefficient of 0.80, dimension reliability values ranging from 0.700 to 0.905, a test–retest reliability value of 0.881, and a scale-level content validity index (S-CVI) value of 0.928. The criterion-related validity value was 0.619. The confirmatory factor analysis (CFA) indicated a good model fit (CMIN/DF = 1.071, RMSEA = 0.08), with factor loadings ≥0.50. The Rasch analysis showed an item reliability value of 1, person reliability values ranging from 0.76 to 0.89, item separation index values ranging from 17.37 to 60.34, and person separation index values ranging from 1.76 to 2.89. The information-weighted fit statistic mean square (infit MNSQ) and outlier-sensitive fit statistic mean square (outfit MNSQ) values for all items ranged from 0.86 to 1.27. Overall, the scale demonstrated good reliability and validity for the Chinese nursing students.ConclusionThe 25-item C-BENEFITS-CCCSAT demonstrates good reliability and validity and can be applied in educational settings to assess students’ ability to provide culturally competent care. Future studies should test the scale in culturally diverse populations to further determine its applicability and generalizability.